2018
DOI: 10.1007/s00590-018-2187-x
|View full text |Cite
|
Sign up to set email alerts
|

Fixation method for treatment of unstable distal clavicle fracture: systematic review and network meta-analysis

Abstract: Surgical management is recommended for unstable distal clavicle fractures. A variety of methods have been previously reported, but there is no current consensus regarding which method is most suitable. Therefore, we have conducted a systematic review and network meta-analysis to compare postoperative shoulder function and complications between different fixation methods to identify which class of fixation is best for unstable distal clavicle fractures. We searched the literature systematically using eligibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 46 publications
0
48
0
2
Order By: Relevance
“…11,26,29,30 However, the incidence of hook-related complications was quite different because the definition of complications also differed in each study. 11,26,29,30 Otherwise, the complication of additional anchor fixation is not well known because previous studies on LCP with additional anchor fixation are still limited. In the present study, we evaluated and defined the complications of additional anchor fixation such as peri-anchor osteolysis and knot-induced skin irritation.…”
Section: Discussionmentioning
confidence: 99%
“…11,26,29,30 However, the incidence of hook-related complications was quite different because the definition of complications also differed in each study. 11,26,29,30 Otherwise, the complication of additional anchor fixation is not well known because previous studies on LCP with additional anchor fixation are still limited. In the present study, we evaluated and defined the complications of additional anchor fixation such as peri-anchor osteolysis and knot-induced skin irritation.…”
Section: Discussionmentioning
confidence: 99%
“…Several surgical techniques have been described including hook plates, locking plates, coracoclavicular screw fixation, and double-button fixation [7]. However, there is no consensus regarding which method is better regarding consolidation, function, and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple surgical techniques have been proposed to manage distal clavicular fractures including the use of a tension band, the modified Weaver-Dunn procedure, and coracoclavicular screw fixation or locking plates [1,7]. None of these techniques have been universally accepted, and each one has its own complications, including wire migration, symptomatic hardware [8], osteolysis of the acromion [9], and migration of the hook into the acromion [10].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis showed that plate and screw fixation and CC fixation should be used as the first-and second-line treatment, respectively, of unstable fractures. 79 Hsu's group showed that the CC loop technique has better outcomes and lower complication rates compared with hook plates. 74 Another group showed that while lock plates and hook plates both achieved good results, patients who were treated with locking plates were able to return to work sooner and had fewer complications than those treated with hook plates.…”
Section: Management Of Distal Clavicular Fracturesmentioning
confidence: 99%